Pelatihan Pembuatan Eco Enzyme dari Sampah Kulit Buah bagi Masyarakat Desa Sorogenen II Kulon Progo - Permadi, Adi; Suharto, Totok Eka; Satar, Ibdal; Chasanah, Alfi; Kurniawan, Agung; Arwini, Arwini; Rahmawati, Daniar; Wahyuni, Denik Putri; Pawenang, Denta Kesdik; Safitri, Harminah; Sumardani, Wahyu Bintoro; Winarni, Winarni; Nafi’, Zahrotun; Suyitno, Suyitno (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
Waste is a problem that has not been resolved properly in Indonesia. Likewise, in Sorogenen II village, Kulon Progo district, where the majority of livelihoods are farmers, gardeners and traders related to agriculture and plantations, there is still not much information on the management of organic waste, especially crop and fruit waste. Several efforts to utilize waste have been made. One way to utilize waste from fresh fruit peels is to ferment it with molasses so that after 3 months it will become eco enzyme. This enzyme liquid has been used as a natural fertilizer, pest repellent, and cleaning liquid. The training conducted by volunteers of the eco enzyme archipelago, PKK group and UAD community service team took place in Sorogenen II village, Kulon Progo district. In addition to the delivery of how to make eco enzyme, the utilization and business opportunities of eco enzyme were also delivered in the training. A showcase of eco enzyme products was also held at UAD and many visitors were enthusiastic about making eco enzyme independently.